2019
DOI: 10.11609/jott.3431.11.9.14101-14111
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and habitats of Paphiopedilum Pfitzer (Orchidaceae) known to occur in Bhutan

Abstract: Paphiopedilum fairrieanum, P. spicerianum, and P. venustum (Orchidaceae: Cypripedioideae) are reported to occur in Bhutan, of which the former is known to be Critically Endangered and the latter two are Endangered.  Based on numerous field trips conducted over the last decade, populations of P. fairrieanum and P. venustum were located in Bhutan.  No individual of P. spicerianum, however, was found despite many search attempts.  Its occurrence in Bhutan may have been originally erroneous.  Based on the accessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Orchid conservation are mainly against habitat loss, climate change and socio-economic exploitation of local populations (Fay, 2018;Gurung et al, 2019). Developmental activities are a threat to orchid conservation and working in conjunction with developmental activities such as road construction and hydro-electric power plant projects can rescue and restore such plant species by National Biodiversity Centre.…”
Section: Introductionmentioning
confidence: 99%
“…Orchid conservation are mainly against habitat loss, climate change and socio-economic exploitation of local populations (Fay, 2018;Gurung et al, 2019). Developmental activities are a threat to orchid conservation and working in conjunction with developmental activities such as road construction and hydro-electric power plant projects can rescue and restore such plant species by National Biodiversity Centre.…”
Section: Introductionmentioning
confidence: 99%
“…Stein is one such species terrestrial in nature found in Bhutan, which is listed as CR by the IUCN. Globally, the orchid is found in Bhutan, India and Nepal [6]. It was found that the population of Paphiopedilum fairrieanum (Lindl.)…”
Section: Introductionmentioning
confidence: 99%
“…The orchid is also known as the lost orchid due to its rarity [9]. According to [6], there are more than 6700 individuals distributed in 10 districts in Bhutan. Paphiopedilum fairrieanum particularly grows on arid, grassy limestone hills at high altitudes [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations